Adult Obesity and Health-Related Quality of Life, Patient Activation, Work Productivity, and Weight Loss Behaviors in the United States - Rozjabek H (Dove Medical Press, 2020)
Heather Rozjabek,1 John Fastenau,1 Anne LaPrade,2 Nikoletta Sternbach2 1Janssen Global Services, Raritan, NJ, USA; 2Kantar, New York, NY, USACorrespondence: John FastenauJanssen Global Services, LLC, 700 US-202, Raritan, NJ 08869, USATel +1 908 429 1872Email JFastena@its.jnj.comIntroduction: While it is generally believed that people living with more severe obesity experience greater negative impacts on health-related quality of life (HRQoL), their experience may be impacted by other factors such as age, gender, and type 2 diabetes mellitus (T2DM).Methods: The 36-Item Short Form Health Survey physical component score and mental component score, Work Productivity and Activity Impairment, and Patient Activation Measure® data from the 2018 National Health and Wellness Survey were analyzed in adults by body mass index (BMI) categories (normal weight: ≥ 18.5–< 25kg/m2, overweight: ≥ 25–< 30kg/m2, class 1 obesity: ≥ 30–< 35kg/m2, class 2 obesity: ≥ 35–< 40kg/m2, class 3 obesity: ≥ 40kg/m2, combined class 2/3 obesity: ≥ 35kg/m2). Findings were further stratified across age groups (young: 18– 35y, middle-aged: 36– 64y, older: ≥ 65y), by gender, and by T2DM status.Results: Overall, as BMI increased people had greater negative effects on HRQoL, felt less involved with and in control of their healthcare, and had greater work productivity and activity impairments. The largest declines were generally observed between class 2 and 3 obesity categories. Young adults with obesity were more likely to feel less engaged with their health care than middle-aged/older adults with obesity. The effects of obesity on HRQoL and patient activation were generally consistent by gender. People with T2DM and obesity tended to have greater declines in physical functioning and more work and activity impairments than people with obesity without T2DM. The proportion of people trying to lose weight increased with increasing BMI category, and people with T2DM were less likely to exercise and more likely to diet than those without T2DM.Conclusion: Increasing levels of obesity tended to have a greater negative impact on HRQoL, patient activation, work productivity, and weight loss behaviors, but some differences in effects by age, gender, and T2DM status were observed.Keywords: obesity, health-related quality of life, HRQoL, activation, productivity, behaviors